2012
DOI: 10.1080/13548506.2011.626432
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions account for variation in positive outlook as well as psychological distress in Rheumatoid Arthritis

Abstract: Psychological distress in rheumatoid arthritis (RA) is associated with adverse clinical outcomes, and appears highly related to patients' illness perceptions. This study aimed to investigate the association between illness perceptions, psychological distress, positive outlook and physical outcomes in RA. Two hundred and thirty patients aged >18 years and prescribed at least one disease-modifying anti-rheumatic drug (DMARD) were recruited from outpatient clinics across Hertfordshire (England). Patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Evidence regarding the influence of positive mental factors such as optimism in treatment response for patients with CIA is scarce 45. There is, however, a study that indicates that perceptions of treatment control are related to a positive outlook in patients with a low level of disease activity,46 and in a recent study, patients with CIA ranked the importance of keeping a positive attitude as high 47…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the influence of positive mental factors such as optimism in treatment response for patients with CIA is scarce 45. There is, however, a study that indicates that perceptions of treatment control are related to a positive outlook in patients with a low level of disease activity,46 and in a recent study, patients with CIA ranked the importance of keeping a positive attitude as high 47…”
Section: Discussionmentioning
confidence: 99%
“…CP patients may experience more pain intensity and psychological distress after they have experienced unsuccessful treatment plans from health care professionals [16]. Psychological distress is associated with poor physical outcomes such as functional disability and pain [27] although the relationship is undoubtedly complex. Tang et al [28] found the presence of mental defeat was a significant predictor of functional disability and distress among individuals with CP.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the patients' feeling of culpability by clarifying wrong beliefs about cause of disease, as well as to reinforce patients' ability to cope with consequences of RA are some strategies that can be adopted by health professionals. Since patients who attribute more symptoms to the rheumatic disease have higher psychological impact, it seems appropriate to help patients to recognize symptoms that are really attributed to RA and to differentiate them from those caused by comorbidities such as depression, anxiety and fibromyalgia [24,28].…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of greater symptomatology and greater stress, beliefs on serious consequences of RA, beliefs on lower ability to handle or cope with disease and beliefs on its owns responsibility in the development of RA were reported to amplify the negative emotional impact of disease and contribute to depressive mood and anxiety [24][25][26][27][28][29].…”
Section: Patient's Beliefs About Ra Influenced Impact Of Disease and mentioning
confidence: 99%